Where Are We Dying? Ethnic Differences in Place of Death Among New Zealanders Dying of Cancer. (27th May 2022) - Gurney, Jason Kevin; Stanley, James; Koea, Jonathan; Adler, Jonathan; Atkinson, June; Sarfati, Diana
Abstract : PURPOSE: Around a third of people with cancer will die outside of their preferred place of death, with substantial variation occurring between and within countries in terms of place of death. Here, we examine place of death within the New Zealand cancer context, with specific focus on differences between Indigenous Māori and other ethnic groups. METHODS: Using national-level data, we identified all those who died in New Zealand between 2007 and 2018 of cancer (N = 107, 373), stratified by ethnicity and cancer type, and linked these patients to national health and mortality records. We then described the crude and age-standardized proportions of cancer deaths by location separately by ethnic group, and conducted logistic regression to compare odds of death within a given location between ethnic groups. RESULTS: After adjusting for age, sex, and deprivation, we found that Māori people with cancer are more likely to die in a private residence than Europeans (46% v 26%; odds ratio [OR] 2.45; 95% CI, 2.36 to 2.55), and also somewhat more likely to die in hospital (27% v 23%; OR 1.26; 95% CI, 1.21 to 1.32). Commensurately, Māori are less likely to die in either hospice inpatient unit (14% v 27%; OR 0.48; 95% CI, 0.45 to 0.51) or residential care (12% v 30%; OR 0.56; 95% CI, 0.52 to 0.59). Pacific patients generally follow the same pattern as Māori patients. These findings were largely repeated across cancer types, with some variation in the magnitude not overall pattern. CONCLUSION: It remains unclear whether these differences reflect differences in preferences for place of death between ethnic groups, or whether they reflect differences in access to appropriate supportive care. Further research is required to examine these differences in greater detail. Abstract :